ADAPTATION OF CHILDREN WITH HEARING AND PRONUNCIATION IMPAIRMENTS WITH COCHLEAR IMPLANTS IN INCLUSIVE EDUCATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
An. The article highlights hearing impaired individuals from the cochlear implant surgery practice prior to surdopedagogic work and cochlear implant surgery practice following surdopedagogic work on and requirements for it. The role and importance of hearing impaired persons in their lives is highlighted by the issues of the need to work with special programs of adaptability to the world of hearing loss.